Effect of Aqueous Extracts of Green Tea in Arsenic induced Toxicity in Mice - Nahid Fatmi1; Naaz Fatima1; M.Z.Shahzada1; Shivdhar Sharma1; Ranjit Kumar2; Mohammad Ali2; Arun Kumar2 (Open Journal of Plant Science - Peertechz Publications, 2017)
Ground water arsenic contamination is a global problem affecting thousands of people worldwide, thus present study was aimed to evaluate the hypothesis that green tea extracts, having high polyphenolic content, might be able to combat the oxidative cellular damage caused by arsenic toxicity and to prevent further development of free radicals. In the present study treatment groups received sodium arsenite orally at the dose of 3 mg kg-1 body weight daily for 4 weeks followed by administration of Camellia sinensis (green tea) 300 mg kg-1 body weight daily by gavage method for 6 weeks. Their biochemical levels like liver and kidney function tests were assayed and were found with elevated levels. Furthermore, their free radical assessment like lipid peroxidation levels were assayed which was found to be many folds higher. But, after administration of aqueous extract of green tea, there was signifi cant amelioration in the biochemical and lipid peroxidation levels. The protective effect of these antioxidants was shown in the form of normalization of enzymatic and non-enzymatic activities represented by normalization of liver and kidney functions.